Aspek Budaya selama Kehamilan pada Masyarakat Suku Jawa - Kartini, Monica; Nurtyashesti Kusumadewi, Berlian (Jurnal Kesehatan, 2022)
Pregnancy is a physiological process, where there are many beliefs, rituals or myths that have been practiced by people from generation to generation to care for the pregnancy in various cultures in the world. The aim of this study is to describe the community’s behaviour or practices related maternity care according to Javanese cultural values. This research is a qualitative descriptive study located in Bulu district, Temanggung regency, Central Jawa. The results:Javanese culture in maternity care, parental advice pregnancy care in Javanese culture, pregnant women awareness for choosing culture in maternity care at the preesent time. The practice of pregnancy care based on cultural aspects is still carried out by the community in the form of dietary restrictions, prohibitions and recommendations in behaviour, and rituals or ceremonies during pregnancy. The development of culturally appropriate health care is very important to provide support for pregnant women during the transition to motherhood, and also to provide culturally sensitive care in overcoming health problems related to aspects of cultural beliefs.